Comparison of two Meta-Heuristics for the Bi-Objective Flexible Job Shop Scheduling Problem with Sequence Dependent Setup Times - Sacramento, João (2021)
The authors gratefully acknowledge the support of the Portuguese National Science Foundation through Portugal 2020 project POCI-01-0145-FEDER-016418 by UE/FEDER through the program COMPETE2020. This work was partially supported by the Fundaçàopara a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UIDB/00297/2020 (Centro de Matemática e Aplicaçôes).